DENTIN SUBSTITUTES: A REVIEW - PRATISHTA JAIN; JAMES D RAJ (International Journal of Pharma and Bio Sciences, 2015)
Dentin substitutes are cements, which have dentin like mechanical properties and can be used as dentin replacements in the tooth crown and root region. The ideal properties of a dentin substitute are biocompatibility, long-term impermeability, antibacterial properties, induction of hard tissue regeneration, stability, non-absorbability, and ease of handling. There are a wide variety of materials that have been used in the past for replacement of dentin. The materials that can be used are calcium hydroxide, glass ionomer cements, mineral trioxide aggregate, and bioactive materials such as biodentine, bioglass and bioceramics. Thus this review briefly describes the above dentin substitutes, their properties, advantages and disadvantages, and their clinical application.